Hubungan Pengetahuan tentang Gizi terhadap Status Gizi Remaja - Peka Yani Lestari; Lensi Natalia Tambunan; Rizki Muji Lestari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Nutrition knowledge is knowledge about selecting ingredients, good food, and daily consumption. Nutritional status is an expression of a person’s nutrition in certain variables, namely poor nutritional status, malnutrition, overnutrition, and obesity. Lack of knowledge about the contributions of nutrition from various types of food will cause health and productivity problems in adolescents it is known that knowledge of nutrition provides provision for adolescents on how to choose healthy foods and understand that food is closely related to nutrition and health. This study aimed to determine the relationship between knowledge of nutrition on nutritional status in adolescents aged 15-18 years. The method used is the literature review research design, with the research subjects being adolescents aged 15-18 years, the literature search using google scholar with literature published in 2017-2020, and literature that is found to be screened based on the inclusion criteria, as well as the analytical method used namely descriptive or narrative that explains narrative in a narrative the findings of the literature. In this study, it was found that from the six journals analyzed; four journals stated a relationship between knowledge about nutrition on the nutritional status of adolescents with each p-value (0,003, 0,0001, 0,001, and 0,021). Then two journals stated that there was no relationship between nutrition knowledge on the nutritional status of adolescents, with p-values of 0,619 and 0,147. There is a significant relationship between knowledge about nutrition with attitudes and behavior in choosing the food consumed. While not their significant relationship because of the lack of applying the knowledge possessed in everyday life.